Cardiovascular and renal outcomes by baseline albuminuria status and renal function: Results from the LEADER randomized trial. Issue 11 (7th August 2020) - Mosenzon, Ofri; Bain, Stephen C.; Heerspink, Hiddo J. L.; Idorn, Thomas; Mann, Johannes F. E.; Persson, Frederik; Pratley, Richard E.; Rasmussen, Søren; Rossing, Peter; von Scholten, Bernt Johan; Raz, Itamar; ,
Abstract: Aim: To assess cardiorenal outcomes by baseline urinary albumin‐to‐creatinine ratio (UACR) and estimated glomerular filtration rate (eGFR) in the contemporary LEADER cohort. Materials and methods: LEADER was a multinational, double‐blind trial. Patients with type 2 diabetes and high cardiovascular (CV) risk were randomized 1:1 to the glucagon‐like peptide‐1 analogue liraglutide (≤1.8 mg daily; n = 4668) or placebo (n = 4672) plus standard care and followed for 3.5 to 5 years. Primary composite outcomes were time to first non‐fatal myocardial infarction, non‐fatal stroke or CV death. Post hoc Cox regression analyses of outcomes by baseline UACR and eGFR subgroups were conducted with adjustment for baseline variables. Results: In the LEADER population, 1598 (17.5%), 2917 (31.9%), 1200 (13.1%), 1611 (17.6%), 845 (9.2%) and 966 (10.6%) had UACR = 0, >0 to <15, 15 to <30, 30 to <100, 100 to <300 and ≥300 mg/g, respectively. Increasing UACR and decreasing eGFR were linked with higher risks of the primary outcome, heart failure hospitalization, a composite renal outcome and death ( P ‐values for the Cochran‐Armitage test for trends were all <.0001). Across UACR and eGFR subgroups, risks of cardiorenal events and death were generally lower or similar with liraglutide versus placebo. Conclusions: In a contemporary type 2 diabetes population, increasing baseline UACR and declining eGFR were linked with higher risks of cardiorenal events and death.